1978
DOI: 10.3758/bf03329720
|View full text |Cite
|
Sign up to set email alerts
|

Stereotyped personality trait ratings of concrete and “typical” stimulus persons

Abstract: Male and female subjects provided ratings of personality traits for students pictured in a large set of facial photographs. Each photograph was rated on each of eight traits. Trait ratings were also provided for subjects' impressions of "typical" male and female college students. Male and female subjects did not differ in their ratings of photographs or of typical students. Sex of the picture (and of the typical student) did reliably influence the ratings for several traits. Certain groups of traits appeared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1989
1989
1991
1991

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
1
2
0
Order By: Relevance
“…The self-descriptions were more stereotyped: male subjects considered themselves to be more masculine and less feminine than the females, as well as less dependable. more of a leader, more self-confident, and less likely to spend time reading and visiting friends, all consistent with traditional sex-role stereotypes (Conover et al. 1978;Widiger & Settle.…”
Section: Sex Role Stereotypessupporting
confidence: 57%
See 2 more Smart Citations
“…The self-descriptions were more stereotyped: male subjects considered themselves to be more masculine and less feminine than the females, as well as less dependable. more of a leader, more self-confident, and less likely to spend time reading and visiting friends, all consistent with traditional sex-role stereotypes (Conover et al. 1978;Widiger & Settle.…”
Section: Sex Role Stereotypessupporting
confidence: 57%
“…Edwards, 1987;Harris et al, 1982;Knoll, 1978;Terry, 1989a;Terry, 1990;Terry & Kroger, 1976). This derogation of the attractiveness of a person who wears glasses, although not universal (Dengerink & Porter, 1984), is not only found for observers but is also characteristic of the person who wears the glasses (Berk, 1963;Knoll, 1978;Terry, 1989a;Terry et al, 1983;Terry & Brady, 1976). It has been suggested that this perception of oneself as less physically attractive leads the wearer to form a "spectacle image" (Berk, 1963), which is associated with self-deprecation, low self-esteem (Terry, 1982;Terry et al, 1983;Terry & Brady, 1976) and anxiety (Terry, 1981;Terry & Zimmerman, 1970).…”
Section: ; Gordingmentioning
confidence: 92%
See 1 more Smart Citation